Tworzenie agencji rządowych – odpowiedź ustawodawcy na potrzeby społeczeństwa - Bieś-Srokosz, Paulina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Political changes in the Polish legal system, which took place in the late 80s of the last century contributed to the creation of new public administration tasks. The State wanted to meet the increasing needs of society, was forced to create new organizational and legal forms to which are included the government agencies. These entities have a special (untypical) features that are not within the traditional sense of the entity of public administration. However, this does not diminish the role or vocation-doe essence of government agencies by the legislature. As one of the main bases of agencies exchanged their performance of public duties that have been entrusted to agencies through separate acts. This article presents issues related not only to the legal nature of government agencies, but also with the impact and importance of the tasks carried out by these entities on Polish society.
Keywords: agencyfication; entity of public administration; special entity of public administration; government agency; public tasks